Effects of time pressure on the amount of information acquired - Peter Letmathe; Elisabeth Noll (International Journal of Business Science & Applied Management (IJBSAM), 2021)
We tested the influence of time pressure and to what extent time pressure interacts with the contextual factors ("payoff scheme" and "level of costs for information that can be acquired") in three laboratory experiments. Participants had to decide how many pieces of information they wanted to purchase non-sequentially in order to make a decision under uncertainty. Our findings indicate that under time pressure, individuals acquire less information. Moreover, while we found no effect of time pressure with a negative payoff scheme, higher levels of information costs suppress the willingness to acquire information.
Keywords: 650; information acquisition; decision-making; amount of information; time pressure; payoff scheme; information costs